PENINGKATAN PENGETAHUAN DENGAN PELAKSANAAN PENYULUHAN TENTANG DIABETES MELITUS DI KAMPUNG WARAS, SARIHARJO, NGAGLIK, SLEMAN, YOGYAKARTA - Faisal Sangadji; Sri Purwati (ABDIMAS Madani, 2019)
Diabetes mellitus is a chronic disease characterized by high blood sugar levels and metabolic disorders in general, which on its way if not controlled properly will cause various complications both acute and chronic. The new IDF consensus advocates early intervention for all people at risk of developing type 2 diabetes, and also focuses on the population health approach. Increasing the knowledge and skills of society, especially those in productive age, is very important in supporting the success of efforts to improve the quality of health. The purposes of this Community Service are to: (1) Increase public knowledge about Diabetes Mellitus; (2) Increase public knowledge about the management of non-pharmacological diabetes mellitus or lifestyle changes, and the use of rational diabetes mellitus drugs; (3) Increase knowledge of people's diet to reduce the risk of being affected / prevent and treat Diabetes Mellitus. The community service activity was conducted by giving lectures, and discussions about diabetes mellitus. The activity increased public awareness to maintain health through the application of a healthy lifestyle; and the curiosity, enthusiasm and active participation. In conclusion, people began to understand about Diabetes Mellitus, its causes, and its non-pharmacological management through lifestyle changes.